The Effect Of Teaching Using The Accelerated Thinking Model On Achievement Students Fifth Scientific Grade In Perspective (Journal of the College of Basic Education, 2024)
The current research aims to identify the effect of teaching with the Acceleration of Thinking model on the achievement of fifth-grade scientific students in perspective subject. For the purpose of verifying the research objectives, the researcher formulated the following null hypothesis (There are no statistically significant differences at the level of significance (0.05) between the average The scores of the experimental group students who studied according to the Acceleration of Thinking Model and the average scores of the control group students who studied according to the regular method on the post-achievement test.) The researcher adopted the experimental method, the experimental design with partial control for the two independent experimental and control groups, and the research population was determined by fifth-grade scientific students in the government morning secondary schools in Baghdad, Rusafa I, for the academic year 2023-2024. The researcher chose the research sample randomly, so it was (1) and its number was (40). student represents the experimental group that studied the educational material (perspective) according to the Acceleration of Thinking model, and Hall (2), which numbered (40) students, represents the control group that studied the educational material according to the traditional method. The researcher built the research tool represented by the achievement test. The test consisted of (20) items, and using the statistical package, the statistical characteristics of the achievement test (validity and reliability) were extracted. After correcting the students' answers, the researcher used the T-test equation for two independent samples to verify the significance of the differences between the two research groups. The results showed that the experimental group that studied the subject matter according to the model of accelerating thinking was superior to their peers in the control group in the academic achievement of the perspective subject among fifth-grade scientific students. The reason is due to the process of organizing the educational experiences included in the educational units according to the model of accelerating thinking, reinforced by artistic paintings and educational activities. In light of the research results, the researcher presented a number of recommendations and a number of proposals.